The cryosphere: an early indicator and global player - Grassl, Hartmut (Polar Research, 1999)
Ice at or below the surface of the planet Earth is an important part of the climate system. The solid phase of water has two unique characteristics which make it both an early indicator of climate change and a global player. First, if warmed to the melting point at 0°C, higher air temperatures and/or higher long-wave back radiation just increase the melting rate but not - as with all other surfaces- the temperature, which stays at 0°C. Small icecaps and mountain glaciers thus become early indicators of a changed climate. Second. If seawater is cooled to the freezing point at about- 1.8"C. the sea ice formation process ejects salt causing the denser water to sink, thereby filling the global ocean interior with very cold water. The location where most of this deep convection occurs is strongly dependent on the freshwater balance and thus on the average salinity of ocean basins. Present ocean configuration and ocean topography, as well as precipitation distribution, make the northern North Atlantic more saline than any other high latitude ocean part and thus the site with most of this deep water formation. Sea ice formation is therefore of high significance for the European climate. Since it drives the near surface warm North Atlantic current northward off the European coast in compensation for southward deep water flow in the western Atlantic, northwestern Europe is warmer by about 4°C than the same latitudes on the eastern Pacific coast of America.
Keywords: Antarktis; isbreer; klimaendringer; kryosfæren; polarområdene; sjøvann; vann

Atmospheric CO₂ and global warming: a critical review - Jaworowski, Zbigniew; Segalstad, Tom Victor; Hisdal, Vidar (Norsk Polarinstitutt, 1992)
Publication Title: Meddelelser
Keywords: Antarktis; atmosfæren; drivhuseffekten; isbreer; karbondioksid; klimaendringer; klimagasser; paleoatmosfæren; temperaturforhold

Do glaciers tell a true atmospheric CO2 story? - Jaworowski, Zbigniew; Segalstad, Tom Victor; Ono, Nobuo (Science of The Total Environment, 1992)
Until 1985 most studies of CO2 in gas inclusions in pre-industrial ice indicated that CO2 concentrations (up to 2450 ppm) were higher than the current atmospheric level. After 1985, lower pre-industrial CO2 values were reported, and used as evidence for a recent man-made CO2 increase. The errors in these revised values, however, are of a similar magnitude to the apparent increase in atmospheric CO2 level. The assumptions used in estimating lower CO2 values in past atmospheres have been: no liquid phase in polar ice; younger age of air than of ice due to free gas exchange between deep firn and the atmosphere; and no change in composition of air inclusions. These assumptions are shown to be invalid. Liquid saline water exists in ice at low temperatures, even below −70°C; airtight ice layers are ubiquitous in Antarctic firn; and more than 20 physico-chemical processes operating in situ and in ice cores contribute to the alteration of the chemical composition of air inclusions. The permeable ice sheet with its capillary liquid network acts as a sieve which redistributes elements, isotopes, and micro-particles. Thirty-six to 100% of air recovered from old ice is contaminated by recent atmospheric air during field and laboratory operations. The value of ∼290 ppm, widely accepted from glacier studies for the pre-industrial atmospheric CO2 level, apparently results from: invalid assumptions; processes in ice sheets; artifacts in ice cores; and arbitrary rejection of high readings. To date, glaciological studies are not able to provide a reliable reconstruction of either the CO2 level in pre-industrial and ancient atmospheres or paleoclimates. Instead these studies have led to a widely accepted false dogma of man-made climatic warming. This dogma may have enormous negative impact on our common future.
URL: https://www.researchgate.net/publication/223504148_Do_glaciers_tell_a_true_atmospheric_CO2_story
Keywords: Antarktis; drivhuseffekt; glasiologi; global oppvarming; isbreer; karbondioksid; paleoklimatologi; stabile isotoper

Virkninger av klimaendringer i polarområdene : bidrag til den interdepartementale klimautredningen - Kverndal, Arnt-Ivar; Elvebakk, Arve; Jaworowski, Zbygniew; Hansson, Rasmus (Norsk Polarinstitutt, 1990)
Publication Title: Norsk Polarinstitutt. Rapportserie
Keywords: Antarktis; biologi; drivhuseffekten; dyreliv; fiskeri; flora; havbruksnæring; havis; havnivå; isbreer; klimaendringer; klimagasser; permafrost; planter; polarområdene; vannressurser; økologi

Aeromagnetic reconnaissance over the Riiser-Larsen Ice Shelf, east Antarctica - Kristoffersen, Yngve; Aalerud, Jan (Polar Research, 1988)
Keywords: Antarktis; glasiologi; havbunnen; isbreer; isfront; seismologi

Iceberg calving and deterioration in Antarctica - Kristensen, Monica (Progress in Physical Geography: Earth and Environment, 1983)
Keywords: Antarktis; glasiologi; innlandsis; isbreer; isbrem; kalving

The response of Antarctic icebergs to ocean waves - Wadhams, Peter; Kristensen, Monica; Orheim, Olav (Journal of Geophysical Research: Oceans, 1983)
The heave, tilt, and strain responses of three Antarctic tabular icebergs to ocean waves were measured during a 1980–1981 cruise of HMS Endurance to the South Atlantic. The three icebergs, located near the South Sandwich and South Orkney islands, were instrumented with accelerometers, tiltmeters, and wire strainmeters, while a Waverider buoy was used to record the ocean wave field. The thickness of the icebergs was surveyed by a helicopter-borne radio echo sounder. The heave response occurred mainly at the swell period but with outbreaks of bobbing which lasted for a few cycles at a resonant period (about 40 s), which agreed well with the predictions of a numerical finite element model. The roll response occurred mainly at a long resonant period (40–50 s), which again agreed well with the model, but there was also a significant response at ocean wave periods (5–20 s), which exceeded predictions. The strain response had a component at very long periods, which is unexplained by theory, while the surface strain at ocean wave periods agreed with the simple analytical model of Goodman et al. (1980). Using this model it is possible to predict a wave height and period that will cause breakup of the icebergs, and we conclude that swell-induced breakup is likely to occur during major storms in the open southern ocean.
Keywords: Sør-Orknøyene; Sørishavet; brehylle; geofysikk; glasiologi; havbølger; isberg; isbreer; isbrem; isfjell; isshelf; oseanografi

Tabular icebergs in ocean waves - Kristensen, Monica; Squire, Vernon A; Moore, Stuart C (Nature, 1982)
Keywords: Antarktis; bølger; ekspedisjoner; glasiologi; havet; isbreer

The glaciers of Bouvetøya - Orheim, Olav (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; glasiologi; isbreer

Glaciological studies by Landsat imaginery of perimeter of Dronning Maud Land, Antarctica - Orheim, Olav (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Dronning Maud Land; NARE ekspedisjoner; geologi; glasiologi; havis; isbreer

Mass transport of Jutulstraumen ice stream in Dronning Maud Land - Gjessing, Yngvar (Norsk Polarinstitutt. Årbok 1970, 1972)
Keywords: Dronning Maud Land; ekspedisjoner; glasiologi; isbreer; isstrøm

A 200-Year Record of Glacier Mass Balance at Deception Island, Southwest Atlantic Ocean, and Its Bearing on Models of Global Climatic Change - Orheim, Olav (The Ohio State University, 1972)
Publication Title: Institute of polar studies. Report
Keywords: Antarktis; ekspedisjoner; glasiologi; isbreer; klimaendringer; meteorologi; storbreen; stratigrafi

On the firn temperatures and glacier flow in Dronning Maud Land - Lunde, Torbjørn (Norsk Polarinstitutt. Årbok 1963, 1965)
Keywords: Dronning Maud Land; firnsnø; glasiologi; isbreer; isstrøm

Et forsøk på måling av breforandring i Antarktis - Liestøl, Olav (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1954)
Publisher: Routledge
Keywords: Antarktis; glasiologi; isbreer; klimaendringer